2010
DOI: 10.1007/s00464-009-0835-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of preoperative Double-J ureteral stenting in retroperitoneal laparoscopic pyelolithotomy

Abstract: D-J stenting and type of renal pelvis influenced the results, i.e., duration of drainage, analgesic requirement, and duration of stay, in patients undergoing RPPL. However, there was no significant difference in operative time, intraoperative blood loss, and postoperative complications. D-J stent group had significant increase in the rate of urinary tract infection postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On the contrary, 1 randomized controlled trial showed that preoperative ureter stenting significantly increased the rate of UTI after RLU. [ 29 ] When symptoms are not significant or pyuria is not detected because of the obstruction of impacted stone, UTI might be missed. Nevertheless, for incident concurrent UTI, on the basis of our previous experience and other reports, RLU is a safe option for obstructive upper ureteral stones, even for those without preoperative indwelling drainage tubes, [ 12 , 30 ] indicating the security of RLU.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, 1 randomized controlled trial showed that preoperative ureter stenting significantly increased the rate of UTI after RLU. [ 29 ] When symptoms are not significant or pyuria is not detected because of the obstruction of impacted stone, UTI might be missed. Nevertheless, for incident concurrent UTI, on the basis of our previous experience and other reports, RLU is a safe option for obstructive upper ureteral stones, even for those without preoperative indwelling drainage tubes, [ 12 , 30 ] indicating the security of RLU.…”
Section: Discussionmentioning
confidence: 99%
“…Chander and colleagues reported that prestenting had no effect on the operation time of retroperitoneal laparoscopic pyelolithotomy. This result was not significant and probably not relevant for the results of ureterorenoscopic stone treatment [1]. …”
Section: Discussionmentioning
confidence: 99%
“…2 Laparoscopic pyelolithotomy (retroperitoneal or transperitoneal) has been proposed as a minimally invasive alternative to open surgery, with high stone clearance rates (range, 75-100%). [5][6][7] According to a retrospective study comparing laparoscopic retroperitoneal pyelolithotomy (n ϭ 16) with PCNL (n ϭ 12), 8 PCNL caused less morbidity and was easier to perform, whereas laparoscopic pyelolithotomy should be reserved for patients who need adjunctive procedures. A similar retrospective study comparing transperitoneal laparoscopic pyelolithotomy and PCNL also showed that the laparoscopic approach is safe but technically challenging and time consuming.…”
Section: Discussionmentioning
confidence: 99%